Cooperation of criminal and executive inspection in case of control with police authorities when receiving information about bringing of the convicted to administrative and criminal responsibility - Чабаненко, Тетяна Валеріївна (Problems of legality, 2016)
The article is devoted to consideration of ways to improve the cooperation of criminal executive inspection with the police regarding the provision of information about administrative and criminal responsibility as to the convicted, released on probation during the period of the probationary period. The author suggests to make changes to the existing order of formation of the police database and the order of obtaining information by criminal and executive inspection about the convicted by means of reflection in the existing police database of information on setting, stay, removals of the convicted and informing by law-enforcement authorities on detention, compilations of the administrative report, entering of data into Pre-Judicial Investigation Unified Register concerning the convicted person who is registered in the relevant criminal and executive inspection.